Sclerosing angiomatoid nodular transformation of spleen: A rare case report - Jyoti Rajpoot; Manjula Jain; Kanika Singh; Aparna Singh; Monica Sarohi; Vikas Tyagi (Wolters Kluwer Medknow Publications, 2024)
Sclerosing angiomatoid nodular transformation (SANT) is a reactive non-neoplastic, rare vascular lesion of the spleen. The histology shows multiple angiomatoid nodules surrounded by proliferative stroma. A 31-year-old lady presented with an abdominal mass for 6 months. Contrast-enhanced computed tomography (CECT) abdomen was suggestive of hemangiopericytoma/hemangioendothelioma. An open splenectomy was performed, and the resected specimen was sent for histopathology examination. The gross examination showed a bosselated mass present at the lower pole of the spleen measuring 8 × 8 cm with peripherally located coalescing red-brown nodules embedded in a dense fibrous stroma on the cut surface. On microscopy, multiple circumscribed angiomatoid nodules comprising irregular slit-like vascular channels lined by plump endothelial cells were seen embedded in dense sclerotic stroma. Because of the lack of specific diagnostic features, it is difficult to diagnose SANT clinically and radiologically. However, the typical histopathological findings are a clue in clinching the diagnosis.